OVERVIEW OF CASH RECEIVINGS AND DISTRIBUTIONS RESTAURANT UNCLE'K CENTER POINT MEDAN - Febriani Laia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
This research was conducted at Restaurant Unclek Center Point Medan. This purpose was to determine Cash Receipts and Expenditures at Restaurant Unclek Center Point Medan. The research method used was data collection methods, namely library methods and field methods with documentation techniques and analytical methods, namely descriptive and analytical methods. deductive method. The results of the study concluded Restaurant Unclek Center Point Medan makes a list of the names of incoming and outgoing items such as cashier equipment and operational items to be recorded in petty cash or petty cash disbursements. Reports of cash receipts and disbursements are adjusted to cash in and out whether balance with expenditure on the remaining money. Each closing cashier recaps the results of sales (turnover) and capital (denominations that function to change guest spending money) in front of the manager and rechecked by the manager before being deposited to the bank. Any excess capital (remaining change in guest spending) is used as cashier's bonus money and processed into employee needs.